2010
DOI: 10.3109/03093646.2010.495370
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Automated Device to Measure Sagittal Plane Stiffness of an Articulated Ankle-Foot Orthosis

Abstract: The purpose of this study was to design a new automated stiffness measurement device which could perform a simultaneous measurement of both dorsi-and plantarflexion angles and the corresponding resistive torque around the rotational centre of an articulated ankle-foot orthosis (AAFO). This was achieved by controlling angular velocities and range of motion in the sagittal plane. The device consisted of a hydraulic servo fatigue testing machine, a torque meter, a potentiometer, a rotary plate and an upright supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…A precedence study showed that stiffness of the oildamper joint was velocity-dependent and enabled stepless adjustment ranging from 0.5 to 1.4 Nm/deg [8]. However, measurement of AFO stiffness is influenced by various experimental factors [4]. A further study is therefore required to transfer the stiffness values applied by the EAFO to a definitive AFO.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A precedence study showed that stiffness of the oildamper joint was velocity-dependent and enabled stepless adjustment ranging from 0.5 to 1.4 Nm/deg [8]. However, measurement of AFO stiffness is influenced by various experimental factors [4]. A further study is therefore required to transfer the stiffness values applied by the EAFO to a definitive AFO.…”
Section: Discussionmentioning
confidence: 98%
“…was measured using a custom-made AFO stiffness measurement device at the angular velocity of 10 deg/s [4]. The results were as follows: designated level 1 (0.32 Nm/deg), level 2 (0.41 Nm/deg), level 3 (0.76 Nm/deg) and level 4 (1.26 Nm/ deg).…”
Section: Design Of the Eafomentioning
confidence: 99%
See 1 more Smart Citation
“…12 The deformation of an AFO would depend on (1) the thickness and design of the structure, (2) the elastic modulus of the material, (3) the fit and firmness of the limb within, and (4) the constraining characteristics of the shoe. These factors would also affect the motion resistance characteristics of an articulated AFO by altering the degree of coalignment of medial and lateral joint components.…”
Section: Discussionmentioning
confidence: 99%
“…In the cases where more than one direction is needed, additional oil dampers need to be installed opposite each other [67], as shown in Figure 7a. The output resistance torque can be adjusted by a screw mechanism [68] and it may be classified into several levels [69]. The amount of stiffness in each level is measured beforehand by using a custom-made AFO stiffness measurement device [69].…”
Section: Damping Stiffness Controlmentioning
confidence: 99%